BEWARE OF THE IMPACT OF STUNTING ON COGNITIVE DEVELOPMENT IN EARLY CHILHOOD - Mentari Yuni Salsabilla; Imaniar Imaniar; Lili Dasa Putri (IKIP Siliwangi Bandung, 2024)
The purpose of making this journal is to analyze how to be aware of the impact of stunting on aspects of cognitive development in early childhood so that we can understand the various impacts of stunting which are increasingly widespread and may be difficult to overcome in a fairly short time. The technique used is a literature review where this research focuses on how to minimize the impact of stunting on aspects of cognitive development in early childhood. By participating in this research, there are several types of information through journals, articles, guidebooks, newspapers and magazines that discuss the impact of stunting on cognitive development in early childhood and case study/literature instruments.